SEMI-QUANTITATIVE EXAMINATION OF TOTAL PROTEIN LEVELS IN DOG SALIVA - Ginting, Brainna Kirayna; Utama, Iwan Harjono; Widyastuti, Srikayati (Buletin Veteriner Udayana, 2023)
Dogs are quite popular animals in the pet category. Maintaining the dog's health as a pet is certainly one of the owner's priorities. On the other hand, the dog is also a major reservoir of various zoonotic disease infections. Early detection and effective, efficient treatment are needed to prevent the spread and increase in the severity of the disease. Saliva, which is one type of biological fluid, has begun to be widely used as a diagnostic sample. Its diverse components not only support each other in carrying out the function of saliva but can also be a biomarker of various infections or diseases in an individual. One of the components of saliva is protein. Protein has been shown to be the biomarker of various types of diseases in humans, such as gingivitis, periodontitis, cancer, and caries. This study examines the total protein level of dog saliva, which carried out on 15 healthy dogs. The saliva samples obtained were measured semi-quantitatively using the urine glucose-protein test kit. This study's data is presented in a frequency distribution of bar graphs and descriptive analyses. The results showed that the total protein levels of dog saliva varied, with the most dominant result being 0–10 mg/dL. Larger sample size and different measuring instruments can be applied in further research.